2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627579
|View full text |Cite
|
Sign up to set email alerts
|

Fourier and wavelet spectral analysis of EMG signals in isometric and dynamic maximal effort exercise

Abstract: Frequency domain analyses of changes in electromyographic (EMG) signals over time are frequently used to assess muscle fatigue. Fourier based approaches are typically used in these analyses, yet Fourier analysis assumes signal stationarity, which is unlikely during dynamic contractions. Wavelet based methods of signal analysis do not assume stationarity and may be more appropriate for joint time-frequency domain analysis. The purpose of this study was to compare Short-Time Fourier Transform (STFT) and Continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Our results corroborate findings of other studies that found no significant differences between the spectral parameters, estimated by FFT and WT, obtained in constant load cycling exercises at submaximal 17 , maximum 18 , or supramaximal 19 intensities, in the comparison between dynamic and isometric exercises 20 and also in dynamic back-muscle exercises 9 as well.…”
Section: Discussionsupporting
confidence: 82%
“…Our results corroborate findings of other studies that found no significant differences between the spectral parameters, estimated by FFT and WT, obtained in constant load cycling exercises at submaximal 17 , maximum 18 , or supramaximal 19 intensities, in the comparison between dynamic and isometric exercises 20 and also in dynamic back-muscle exercises 9 as well.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies compared the use of CWT and STFT in different exercises protocols [7] [9] [15] [16]. Both techniques seem to provide similar information regarding muscular fatigue, when EMG fatigue indices are assessed in dynamic exercise systematically controlling the movement speed, angle and force.…”
Section: Discussionmentioning
confidence: 99%
“…However, for this study in addition to the RMS also analyzed spectral parameters. To spectral analyses or frequency domain, was obtained the parameters from median frequency (MF), variance and slope, those values were determined using Wavelet Daubechies db4 (DWT) [6,8]. Was considered the analyses of EMG signal in the contraction phase (bursts) and during all signal (bursts + silence).…”
Section: Influence Of the Burst And Silence In Treatment Of Emg Signamentioning
confidence: 99%
“…To find and use the spectrum, we must find a source that gives us the possibility to produce this figure, when sometimes the Fast Fourier Transform proves as algorithm in a simple calculus to find discrete signals. A series of recommendations are proposed to this technique, since the establishment of sample number, duration intervals, window apply and many aspects as signal stationary is a complicated thing to deal with, which leads us to use a wavelet transform, more appropriate to cyclic activities as cycling and running for example [6][7][8][9].…”
Section: Time and Frequency Domainmentioning
confidence: 99%